مرک و ماتم نا دود آک: Death Customs in Oral Brahui literature - Abbas, Amina (Al-Burz, 2010)
The history of subcontinent shows that the Brahui known as nomadic Besides Balochistan they also live in Panjab, Sindh, Khaeber, Pakhtoon khawa Brahui is the major tribe of Baloch the Brahui speakers live in Jahlavan and Saravan this research paper reflects the customs and old tradition of Baloch.